Impact of a Patient Blood Management monitoring and feedback programme on allogeneic blood transfusions and related costs. (25th August 2019) - Kaserer, A.; Rössler, J.; Braun, J.; Farokhzad, F.; Pape, H.‐C.; Dutkowski, P.; Plass, A.; Horisberger, T.; Volbracht, J.; Manz, M. G.; Spahn, D. R.
Summary: A Patient Blood Management programme was established at the University Hospital of Zurich, along with a monitoring and feedback programme, at the beginning of 2014 with a first analysis reported in 2015. Our study aimed to investigate the further impact of this Patient Blood Management monitoring and feedback programme on transfusion requirements and related costs. We included adult patients discharged between 2012 and 2017. A total of 213, 882 patients underwent analysis: 66, 659 patients in the baseline period (2012–2013); 35, 309 patients in the year after the introduction of the Patient Blood Management monitoring and feedback programme (2014) and 111, 914 patients in the continued sustainability period (2015–2017). The introduction of the Patient Blood Management monitoring and feedback programme reduced allogeneic blood product transfusions by 35%, from 825 units per 1000 hospital discharges in 2012 to 536 units in 2017. The most sustained effect was an approximately 40% reduction in red blood cell transfusions, from 535 per 1000 discharges to 319 units. Fewer patients were transfused in the periods after the introduction of the Patient Blood Management monitoring and feedback programme (6251 (9.4%) vs. 2932 (8.3%) vs. 8196 (7.3%); p < 0.001). Compared with 2012, the yearly OR for being exposed to any blood transfusion declined steadily after the introduction of the Patient Blood Management monitoring and feedback programme to 0.64 (95%CI 0.61–0.68; p < 0.001) in 2017. For patients requiring extracorporeal membrane oxygenation, transfusion requirements were also sustainably reduced. This reduction in allogeneic blood transfusions led to savings of 12, 713, 754 Swiss francs (£ 9, 497, 000 sterling; EUR 11, 100, 000; US$ 12, 440, 000) in blood product acquisition costs over 4 years. In‐hospital mortality was not affected by the programme. The Patient Blood Management monitoring and feedback programme sustainably reduced transfusion requirements and related costs, without affecting in‐hospital mortality. Abstract : 환자 혈액 관리 프로그램은 모니터링 및 피드백 프로그램으 로 구성되어 2014년 초 취리히 대학병원(University Hospital of Zurich)에 처음 도입되었으며, 2015년에 이에 대한 첫 분석 을 수행하였다. 본 연구는 이 환자 혈액 관리 모니터링 및 피 드백 프로그램이 수혈 요구량 및 관련 비용에 미치는 추가 영 향을 조사하는 것을 목표로 하였다. 2012년에서 2017년 사이 에 퇴원한 성인 환자를 대상으로 하였다. 총 213, 882명의 환자 를 분석하였는데, 기준 기간(baseline period, 2012‐2013년) 에 66, 659명, 환자 혈액 관리 모니터링 및 피드백 프로그램 도 입 후 1년간(2014년) 35, 309명, 이후 지속 가능 기간 (continued sustainability period, 2015‐2017년)에 111, 914명 이 포함되었다. 환자 혈액 관리 모니터링 및 피드백 프로그램 의 도입은 동종 이형 혈액 제제의 수혈을 35%까지 줄였는데, 즉, 2012년의 퇴원 1000회당 825단위에서 2017년의 516단위로 감소하였다. 이 중에 가장 지속적인 효과를 보인 것은 적혈구 수혈로, 퇴원 1000회당 535단위에서 319단위로 약 40% 감소하였다. 환자 혈액 관리 모니터링 및 피드백 프로그램의 도입 후 기간들에서 더 적은 환자들이 수혈을 받은 것으로 나타났 다(기준 기간 6, 251명[9.4%] vs. 도입 후 1년간 2, 932명[8.3%] vs. 지속 가능 기간 8, 196명[7.3%], p ‹ 0.001). 2012년과 비교 하였을 때, 환자 혈액 관리 모니터링 및 피드백 프로그램을 도 입한 이후 모든 종류의 혈액 수혈에 노출될 연간 교차비(odds ratio)가 꾸준히 감소하여 2017년에는 0.64 (95% 신뢰구간 0.61–0.68, p ‹ 0.001)로 나타났다. 또한 체외막산소공급 (extracorporeal membrane oxygenation)이 필요한 환자에 서의 수혈 요구량이 지속적으로 감소하였다. 동종 이형 혈액 수혈의 감소로 인해 4년간 혈액 제제 취득 비용에 있어서 12, 713, 754스위스프랑(9, 497, 000파운드, 11, 100, 000유로, 12, 440, 000미국달러)이 절감되었다. 병원 내 사망률은 본 프로 그램의 영향을 받지 않았다. 환자 혈액 관리 모니터링 및 피드 백 프로그램은 병원 내 사망률에 영향을 미치지 않으면서 수 혈 요구량 및 관련 비용을 지속적으로 감소시켰다.